Some Properties and Antioxidant Potential of Olives and Their Corresponding Extra Virgin Olive Oils in Turkey - Mutlu Keceli, Turkan (Asian Journal of Chemistry, 2013)
Some of the properties of olives and their corresponding extra virgin olive oils were evaluated. It was found that variety has significant effect on properties and antioxidant activity of olives and their corresponding extra virgin olive oils. Ayvalik, Nizip and Odemis olives had higher oil content and their corresponding extra virgin olive oils had higher chlorophyll, caretenoid content (p < 0.05). Ayvalik, Halhali, Hasebi, Nizip and Odemis olive extracts were more effective as radical scavenger than BHT and BHA (p < 0.05). Ayvalik, Nizip and Odemis olive extracts showed better or similar antioxidant activity in bulk refined olive oil than control, BHT and BHA (p < 0.05). Halhali, Nizip and Odemis extra virgin olive oil extracts showed better protection in refined olive oil-in-water emulsions than control, BHT and BHA (p £ 0.05). It was concluded that extracts from some olives and extra virgin olive oils may have food additive value for oils and oil containing foods.